2009
DOI: 10.1128/mcb.01054-08
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cofactor Requirements for Histone Eviction from Two Nucleosomes at the Yeast PHO84 Promoter Are Determined by Intrinsic Nucleosome Stability

Abstract: We showed previously that the strong PHO5 promoter is less dependent on chromatin cofactors than the weaker coregulated PHO8 promoter. In this study we asked if chromatin remodeling at the even stronger PHO84 promoter was correspondingly less cofactor dependent. The repressed PHO84 promoter showed a short hypersensitive region that was flanked upstream and downstream by a positioned nucleosome and contained two transactivator Pho4 sites. Promoter induction generated an extensive hypersensitive and histone-depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(72 citation statements)
references
References 89 publications
5
67
0
Order By: Relevance
“…However, a later study showed that the number of nucleosomes at the PHO5 promoter in pho80 gcn5 yeast was unchanged relative to the repressed state in wild type yeast, implying that histone eviction did not occur (68). Similarly, at the yeast PHO84 promoter, activation is accompanied by increased accessibility to the restriction enzyme HpaI and histone eviction in wild type yeast, whereas in gcn5 mutant yeast, a delay in transcriptional induction is accompanied by a corresponding delay in histone eviction, with no alteration in the kinetics of increased HpaI accessibility (69). In another example, activation of the yeast RNR3 promoter in response to DNA damage results in altered MNase cleavage and histone eviction in wild type yeast.…”
Section: Discussionmentioning
confidence: 91%
“…However, a later study showed that the number of nucleosomes at the PHO5 promoter in pho80 gcn5 yeast was unchanged relative to the repressed state in wild type yeast, implying that histone eviction did not occur (68). Similarly, at the yeast PHO84 promoter, activation is accompanied by increased accessibility to the restriction enzyme HpaI and histone eviction in wild type yeast, whereas in gcn5 mutant yeast, a delay in transcriptional induction is accompanied by a corresponding delay in histone eviction, with no alteration in the kinetics of increased HpaI accessibility (69). In another example, activation of the yeast RNR3 promoter in response to DNA damage results in altered MNase cleavage and histone eviction in wild type yeast.…”
Section: Discussionmentioning
confidence: 91%
“…This dilemma is evident in the case of activation of the PHO5, PHO8, and PHO84 genes in yeast, where INO80 and SWI/SNF both activate transcription in independent manners (3,53). Our study delineates the intrinsic differences between INO80 and SWI/SNF and points to how they may increase accessibility of chromatinized DNA in distinct ways.…”
Section: Discussionmentioning
confidence: 87%
“…Both INO80 and SWI/SNF have been shown to act on the PHO5 and PHO8 promoters (3,17,18,53). INO80 mostly recently was found to be involved in DNA repair (33,49).…”
mentioning
confidence: 99%
“…Of these, only Swi/Snf (4,16,21,43) and Ino80 (4,59) are involved in opening of the PHO5 promoter, to an extent where their absence causes a measurable delay. The same is true for the histone acetyltransferases Gcn5 (7,24) and Rtt109 (66,67) and the histone chaperones Asf1 (1,32) and Nap1 (15). The degree of cofactor dependency varies with the degree of PHO5 induction (16,32).…”
mentioning
confidence: 79%